The Influence Of Environmental, Social, Governance (ESG) Disclosures On Financial Performance - Setiawati, Asri; Hidayat, Taufiq (STIE Indonesia Banking School, 2023)
Research purposes. This research aims to examine the effect of disclosure of environmental performance, social performance, governance performance (ESG) on company financial performance as proxied by Return on Assets (ROA). Research methods. Data analysis This research uses panel data regression analysis. The research used 13 samples of KBMI 3 and 4 bank financial industry companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The sample was selected using a purpose sampling technique. This research uses the Return on Assets (ROA) proxy as financial performance. Research Results and Findings. The test results show that individually there is no significant effect of disclosure of environmental performance, social performance, governance performance (ESG) on the company's financial performance.